Perceptions of Electric Vehicle Adoption among Young Adults in Ahmedabad: Exploring Influences and Implications - Mehta, Hitarth; Rathod, Lakshita; Shah, Fenil; Bhatt, Aum; Machhvara, Jenil; Chauhan, Rahul; Maseleno, Andino (Greenation International Journal of Engineering Science, 2023)
This study explores the perceptions of young adults aged 18-30 in Ahmedabad, India, toward electric vehicle (EV) adoption. A quantitative approach was employed, gathering data from 104 respondents via a structured questionnaire. Key factors examined include vehicle preference, peer influence, and promotion of EVs. One-way ANOVA results indicated that age did not significantly impact these factors, suggesting that other variables, such as environmental concerns and technological advancements, may have a stronger influence on purchase intentions. The study highlights the growing awareness of sustainability and technology among youth, with implications for targeted marketing strategies. The research provides a foundation for future studies on EV adoption across different regions and age groups. Additionally, the findings contribute to the global conversation on reducing carbon emissions and increasing EV adoption for a sustainable future.